1996
DOI: 10.1021/jp953100d
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Structures, and Reactivities of Niobium Oxide Cluster Ions

Abstract: Niobium oxide cluster ions are produced by a laser-induced plasma source. The cluster distribution, collision-induced dissociation (CID), and cluster reactivities are studied using a triple-quadrupole mass spectrometer. CID experiments on the cluster ions Nb3O7 - 9 +, Nb4O9 - 11 +, and Nb5O12 + reveal that their building blocks are Nb2O5, NbO2 +, NbO3, Nb3O7 +, O, and O2, whereby the cluster stoichiometry is assigned to have the general form (NbO3) m (NbO2) n (O)0 - 4 +. The trends in the ionization potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 32 publications
4
94
2
Order By: Relevance
“…26,30 With regard to reactivity, Castleman and co-workers found that the cluster size and the degree of coordinative saturation affect the reactivity of the cationic clusters with n-butane and that cationic clusters with a somewhat metal-rich character can abstract an oxygen atom from acetone. 25,31,32 As for anionic clusters, Jackson and co-workers have reported that Nb x O y − compounds undergo different reactions with methanol and ethanol depending on the oxidation state of Nb and the number of Nb−O double bonds. 29 In our previous study, we showed that the combination of coverage-dependent 2PPE measurements and DFT calculations is a highly effective tool for understanding electron transfer at the cluster−support interface for a series of metal oxide nanoclusters on Cu(111).…”
Section: O 10mentioning
confidence: 99%
“…26,30 With regard to reactivity, Castleman and co-workers found that the cluster size and the degree of coordinative saturation affect the reactivity of the cationic clusters with n-butane and that cationic clusters with a somewhat metal-rich character can abstract an oxygen atom from acetone. 25,31,32 As for anionic clusters, Jackson and co-workers have reported that Nb x O y − compounds undergo different reactions with methanol and ethanol depending on the oxidation state of Nb and the number of Nb−O double bonds. 29 In our previous study, we showed that the combination of coverage-dependent 2PPE measurements and DFT calculations is a highly effective tool for understanding electron transfer at the cluster−support interface for a series of metal oxide nanoclusters on Cu(111).…”
Section: O 10mentioning
confidence: 99%
“…[24][25][26] We investigated the structure and bonding of early transition metal oxide clusters using a combined photoelectron spectroscopy (PES) and theoretical approach with the aim of discovering specific structures or clusters that may mimic a catalytic site. [27,28] Our experiment was carried out with a magnetic-bottle PES apparatus with a laser vaporization cluster source.…”
mentioning
confidence: 99%
“…Numerous groups have applied CID to investigate a wide variety of cluster systems (e.g. metal [10], metal oxide [11], carbon [12] and silicon [13] clusters). Particularly, for Ti x O + y clusters, Yu and Freas [1] have investigated the CID of mass selected Ti x O + y complexes produced by fast-atom-bombardment on Ti-foils and TiO 2 -powders.…”
Section: Introductionmentioning
confidence: 99%